Multifunctional Nanodrug‐Mediated Immunotherapy in Microsatellite Stable Colorectal Cancer via Promoting m6A Modification and M1‐Like Tumor‐Associated Macrophages Polarization - Caiying Li; Gengjia Chen; Tan Li; Peiyi Xie; Decai Ma; Long Yang; Zecong Xiao; Xintao Shuai; Xiaochun Meng (Small Structures, 2024)
Immunotherapy has made great progress in various solid tumors. However, the “cold” tumor immune microenvironment of microsatellite stable subtype colorectal cancer (MSS‐CRC) hinders the effectiveness of immunotherapy. Therefore, reshaping the immunosuppressive microenvironment and initiating efficient antitumor immune responses are critical for immunotherapy of MSS‐CRC. According to the analysis of clinical samples, it is found that the levels of fat mass and obesity‐associated protein (FTO) and M2‐like tumor‐associated macrophages (TAMs) infiltration are significantly elevated in CRC tissue, which has driven one to construct a targeted cationic liposome to simultaneously enhance the RNA methylation and inhibit the CD47 immune checkpoint expression of tumor cells in the hope of promoting the M1‐like TAMs polarization and phagocytosis. By upregulating the m6A modification of tumor cells, the lactate secretion is decreased to promote the TAMs repolarized into M1‐like. Meanwhile, CD47 siRNA codelivered by the cationic liposomes downregulates the expression of immune checkpoint CD47 on the cancer cell surface, which enhances the phagocytic ability of the M1‐like TAMs. The combination treatment scheme is expected to provide a new option for treating MSS‐CRC, which may also be extended for treating other immunologically “cold” tumors.